The The Relationship Between Nurses’ Caring Attitudes and Anxiety Levels Among Patients’ Families in Intensive Care Units - Fadila Nurlita Septiani; Popon Haryeti; Ayu Prameswari Kusuma Astuti (Inspirasi Foundation, 2026)
Introduction: Families of critically ill patients in intensive care units often experience anxiety due to uncertain prognosis and unfamiliar medical environments. Nurses' caring behaviors play a crucial role in reducing family anxiety, but empirical evidence in Indonesian regional hospitals is limited. Objective: This study aimed to identify the relationship between nurses' caring attitudes and family anxiety levels in the intensive care unit of a regional general hospital. Method: A cross-sectional correlational study was conducted with 65 family members of ICU and NICU patients selected through simple random sampling. Data were collected using the Caring Behavior Inventory (CBI-24) and the Hamilton Anxiety Rating Scale (HARS), analyzed using Spearman's rank correlation. Result: The majority of nurses demonstrated good caring attitudes (73.8%), with the highest professional knowledge (83.1%) and the lowest respect (64.6%). Family anxiety was mostly mild (44.6%) or absent (38.5%), with only 3.1% experiencing severe anxiety. Spearman analysis revealed a significant negative correlation (r=-0.352; p=0.004), indicating that higher caring attitudes were associated with lower family anxiety. Conclusion: There is a significant negative relationship between nurses' caring attitudes and family anxiety in intensive care settings. These findings support the implementation of standardized care protocols, therapeutic communication training, and a family-centered care approach to optimize nursing quality in regional hospitals in Indonesia.